František Antonín z Dietrichsteina (1643–1721) – šlechtic v řadách Tovaryšstva Ježíšova - Zuzana Orálková (Theatrum Historiae)
The study deals with the personality of Franz Anton von Dietrichstein and his (seemingly) sudden decision to enter the Jesuit order during his study stay in Rome in 1666 and resign from the already acquired canonry in Passau, Regensburg and Olomouc. The article works with the correspondence kept by Franz Anton and his tutor Josef Seim with prince Ferdinand von Dietrichstein, Franz´s half-brother and legal guardian, and tries to analyze in what way Franz could arrive at this decision, why it was problematic for his family and how this new situation, which in the end really resulted in Franz´s entry into the novitiate, was perceived. At the same time, the paper tries to present this individual story in the context of the present knowledge of the church and religious order career of the nobility. The second part of the study represents Franz's decision and his subsequent order life from the perspective of his post-mortem elogium from 1721.